INPUT DATA COLLECTION FOR THE FIT-GAP ANALYSIS METHOD: A LITERATURE REVIEW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Development of Enterprise Resource Planning (ERP) systems has become an independent industry for the improvement of information systems. It can be stated that ERP systems are designed to support the operation of a company. The fundamental objective of the system is to create a business value that aims at reducing the time and costs of the business while increasing the profit of the company. Although the adaptation and deployment of the ERP system, in general, are complex and protracted processes that require a lot of resources, the obtained results sometimes differ from the expected results of users. Mostly for that reason, there are incomplete internal enterprise business processes and software requirements analysis and development. Therefore, there is a need to determine the compliance of the main enterprise requirements and business processes with the ERP system. To choose the most appropriate ERP system, it is necessary to identify all possible methods of input data for the fit-gap analysis method. Thus, the main aim of the present study is to identify possible input data for the fit-gap analysis method, which can be used for the selection of the most appropriate ERP system.